The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1590/s0004-27492001000400006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de glaucoma identificada em campanha de detecção em São Paulo

Abstract: Objetivo: Descrever os achados de um programa de detecção de glaucoma em São Paulo dando-se ênfase para dados de prevalência de glaucoma e doenças associadas. Métodos: Durante uma semana, em agosto de 1997, foi realizada no Hospital do Servidor Público Estadual de São Paulo, uma campanha de detecção de glaucoma. Durante este período, 1438 pacientes com idade variando entre 40 e 87 anos (média de 58,24 ± 10,88 anos), foram examinados quanto ao glaucoma. Idade mínima de 40 anos foi utilizada como critério de inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
1
1
1
9
Order By: Relevance
“…There are few Brazilian population studies, mostly involving non-institutionalized individuals, and there is no regional epidemiological data on the prevalence of glaucoma. In general, the literature data was obtained in ambulatories of university hospitals or targeted campaigns, consisting of 7.3% of glaucoma patients in the city of São Paulo in a population sample of other age group (40 to 87 years, average age 58.24 ± 10.88 years) (11) , data much higher the stated in the present study. A population study in southern Brazil found a prevalence of 3.4% of glaucoma patients in individuals above 40 years, an age group in which the prevalence of glaucoma is higher (12) .…”
Section: Table1contrasting
confidence: 43%
“…There are few Brazilian population studies, mostly involving non-institutionalized individuals, and there is no regional epidemiological data on the prevalence of glaucoma. In general, the literature data was obtained in ambulatories of university hospitals or targeted campaigns, consisting of 7.3% of glaucoma patients in the city of São Paulo in a population sample of other age group (40 to 87 years, average age 58.24 ± 10.88 years) (11) , data much higher the stated in the present study. A population study in southern Brazil found a prevalence of 3.4% of glaucoma patients in individuals above 40 years, an age group in which the prevalence of glaucoma is higher (12) .…”
Section: Table1contrasting
confidence: 43%
“…Foi focada para a detecção objetiva de alterações oculares através da medida da AV, tonometria e fundoscopia realizados no mesmo dia e no próprio local onde se realizava o evento, mas vários pacientes tiveram que ser encaminhados para segundo atendimento para manejo de outras situações encontradas. Não foram encontrados casos suspeitos de glaucoma, apesar da prevalência importante observada em outros programas de detecção de glaucoma: 7,3% a 7,8% (11)(12) . A prevalência de glaucoma aumenta com o avanço da idade.…”
Section: Tabela 1 Resumo Das Campanhas De Promoção De Saúde Ocular Reunclassified
“…Estimase que cerca de 66,8 milhões de pessoas sejam portadoras dessa patologia e, dessas, 6,7 milhões sejam bilateralmente cegas. No Brasil em torno de 4 a 6% da população acima dos 40 anos possui a doença e não sabe (3,5) .…”
Section: Introductionunclassified